2023
DOI: 10.1038/s41467-023-39615-x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational restriction shapes the inhibition of a multidrug efflux adaptor protein

Abstract: Membrane efflux pumps play a major role in bacterial multidrug resistance. The tripartite multidrug efflux pump system from Escherichia coli, AcrAB-TolC, is a target for inhibition to lessen resistance development and restore antibiotic efficacy, with homologs in other ESKAPE pathogens. Here, we rationalize a mechanism of inhibition against the periplasmic adaptor protein, AcrA, using a combination of hydrogen/deuterium exchange mass spectrometry, cellular efflux assays, and molecular dynamics simulations. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…A combination of computational (ensemble docking) and experimental approaches ( in vitro AcrA binding studies using surface plasmon resonance, as well as in vivo limited proteolysis) suggested that both compounds target AcrA, the MFP/PAP component of the tripartite AcrAB-TolC complex. NSC60339 is thought to bind to the hinge region (linking α-hairpin- and lipoyl-domains) of AcrA, thereby constricting conformational flexibility and reducing its ability to transduce signal to AcrB possibly inhibiting functional rotation and efflux [182]. NSC33353, however, is suggested to bind the AcrA membrane proximal (MP) domain (), presumably interfering with functional interactions between AcrA and AcrB.…”
Section: Efflux Pump Inhibitorsmentioning
confidence: 99%
“…A combination of computational (ensemble docking) and experimental approaches ( in vitro AcrA binding studies using surface plasmon resonance, as well as in vivo limited proteolysis) suggested that both compounds target AcrA, the MFP/PAP component of the tripartite AcrAB-TolC complex. NSC60339 is thought to bind to the hinge region (linking α-hairpin- and lipoyl-domains) of AcrA, thereby constricting conformational flexibility and reducing its ability to transduce signal to AcrB possibly inhibiting functional rotation and efflux [182]. NSC33353, however, is suggested to bind the AcrA membrane proximal (MP) domain (), presumably interfering with functional interactions between AcrA and AcrB.…”
Section: Efflux Pump Inhibitorsmentioning
confidence: 99%
“…These scientists used a "molecular wedge" technique, primarily a compound known as NSC 60339, that could successfully disrupt the function of bacterial efflux pumps. The resulting disruption prevents bacteria from releasing antibiotics, increasing the efficacy of these antimicrobial agents against bacterial infections [133].…”
Section: Other Biofilm Inhibitorsmentioning
confidence: 99%
“…Periplasmic proteins are convenient targets for the development of new antivirulence agents or antibiotic adjuvants against Gram-negative bacteria ( Pandeya et al, 2020 ). The recently exploited periplasmic targets include, e.g., AcrA—acriflavine resistance protein A (its inactivation results in increased sensitivity to many antimicrobials) ( Russel Lewis et al, 2023 ), MtrD—resistance-nodulation-cell division (RND) family transporter protein (its inhibition impairs the function of the multidrug efflux pomp) ( Lyu et al, 2022 ), SurA—periplasmic chaperone (its inhibition results in increased antibiotic susceptibility and decreased virulence) ( Bell et al, 2018 ), LptA—lipopolysaccharide transport protein (its inhibition alters or blocs transport of lipopolysaccharides) ( Sinha et al, 2022 ), and PelA—deacylase (its inhibition leads to disruption of exopolysaccharide production and biofilm formation) ( Razvi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%